South Pacific quasi-stationary waves and anomalously cold summers in the northernmost Antarctic Peninsula - Costa, Alfredo J. (2012)
The present work aims to analyze the tropospheric circulation in the Southern Hemisphere (SH) associated with anomalously cold summers (ACS, Dec-Feb) in the period 1981-2010 over northernmost Antarctic Peninsula (AP). A quartile criterion is used to identify ACSs, and a wave-activity flux for stationary quasi-geostrophic (QG) eddies on a zonally varying basic flow is used as a diagnostic tool to study wave-train propagation from the Pacific Ocean. It is shown that the summer of 2010 was singularly cold, so this summer is studied separately from the ACS composites previous to 2010. The ACSs prior to 2010 are characterized by a Pacific-South American (PSA)-like quasi-stationary wave (QSW) train that extends barotropically through the troposphere up to the lower stratosphere. It is emanated from a region of anomalous convection in New Zealand and it is directed towards the South Pacific. The wave train leads to an anomalous stationary cyclone that is located to the northwest of the AP. The easterly wind anomalies induced by this local anomalous stationary cyclone together with higher cloudiness anomalies are found to be associated with ACS events over the northern AP. The 2010 cold summer not only shows an anomalous stationary cyclone to the northwest of the AP, but singularly also shows a mid-latitude anomalous anticyclone over the south-eastern South Pacific. From there, a shorter QSW regionally propagates towards southern South America. In this case there is no PSA-like wave structure crossing the South Pacific. The short regional QSW seems to emanate from a region of positive sea surface temperature (SST) anomalies in the middle of the southern South Pacific. The SST anomalies can be related to the generation of locally increased mean-flow baroclinicity. Hence, this QSW propagation is related to anomalous transient activity. In turn, these SST anomalies could be induced by a PSA-like QSW propagation during the previous spring (Sep-Nov) of 2009.